Apatinib as second-line or later therapy in patients with advanced hepatocellular carcinoma (AHELP): a multicentre, double-blind, randomised, placebo-controlled, phase 3 trial. (July 2021) - Qin, Shukui; Li, Qiu; Gu, Shanzhi; Chen, Xiaoming; Lin, Lizhu; Wang, Zishu; Xu, Aibing; Chen, Xi; Zhou, Cuncai; Ren, Zhenggang; Yang, Lin; Xu, Li; et al.
Summary: Background: Inhibition of vascular endothelial growth factor receptor (VEGFR) has shown antitumour activity in advanced hepatocellular carcinoma, but few studies of VEGFR inhibitors have been done in populations with a high prevalence of hepatitis B virus infection. The aim of this study was to evaluate the efficacy and safety of apatinib in patients with pretreated advanced hepatocellular carcinoma. Methods: AHELP was a randomised, double-blind, placebo-controlled, phase 3 trial done at 31 hospitals in China, in patients (aged ≥18 years) with advanced hepatocellular carcinoma who had previously been refractory or intolerant to at least one line of systemic chemotherapy or targeted therapy. Patients were randomly assigned (2:1) to receive apatinib 750 mg or placebo orally once daily in 28-day treatment cycles. Group allocation was done with a central randomisation system, with a block size of six, and was stratified by Eastern Cooperative Oncology Group performance status, previous sorafenib treatment, and presence of vascular invasion or extrahepatic metastasis. The primary endpoint was overall survival, which was defined as time from randomisation to death from any cause, and was analysed in patients who were randomly assigned and received at least one dose of the study drug. Safety analyses were done in patients who received at least one dose of the study treatment and had post-dose safety assessments. This trial is registered with ClinicalTrials.gov, NCT02329860 . Findings: Between April 1, 2014, and May 3, 2017, 400 eligible patients were randomly assigned to receive apatinib (n=267) or placebo (n=133). Seven patients (six in the apatinib group and one in the placebo group) did not receive study treatment and were excluded from efficacy analyses. Overall survival was significantly improved in the apatinib group compared with the placebo group (median 8·7 months [95% CI 7·5‒9·8] vs 6·8 months [5·7‒9·1]; hazard ratio 0·785 [95% CI 0·617‒0·998], p=0·048). 387 patients (257 in the apatinib group and 130 in the placebo group) had a safety assessment after study treatment and were included in safety analyses. The most common treatment-related adverse events of grade 3 or 4 were hypertension (71 [28%] patients in the apatinib group vs three [2%] in the placebo group), hand–foot syndrome (46 [18%] vs none), and decreased platelet count (34 [13%] vs one [1%]). 24 (9%) patients in the apatinib group and 13 (10%) in the placebo group died due to adverse events, but none of these deaths were deemed to be related to treatment by investigators. Interpretation: Apatinib significantly improved overall survival in patients with pretreated advanced hepatocellular carcinoma compared with placebo, with a manageable safety profile. Funding: Jiangsu Hengrui Medicine.